The second constitutional era and İttihat ve Terakki in the works of Ömer Seyfettin [Ömer Seyfettin'in eserlerinde II. Meşrutiyet ve İttihat ve Terakki] - (:unkn) unknown (My University, 2008)
Ömer Seyfettin (1884-1920) is well-known for his short stories, poems, prose poems and translations. As a writer, he was always interested in the social and political events of his time, which he reflected in his works. The declaration of the Second Constitutional Monarchy and the issues surrounding İttihat ve Terakki Partisi (The Union and Progress Party) occupy an important place in his works. In this study the views of Ömer Seyfettin on the Second Constitutional Era and the İttihat ve Terakki are evaluated. © Ahmet Yesevi University Board of Trustees.
Keywords: İttihat ve terakki partisi; Ömer seyfettin; The second constitutional era